2013
DOI: 10.1074/jbc.m113.457242
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Novel Endoplasmic Reticulum Stress Response Element Regulated by XBP1

Abstract: Background: Endoplasmic reticulum (ER) stress maintains cellular protein homeostasis. Results: A novel ER stress-responsive element, ERSE-26, identified in 38 genes, is regulated by sXBP1 during ER stress. Conclusion: ER stress increases levels of prion and other proteins not previously known to be involved in the ER stress response. Significance: ERSE-26 implicates novel genes regulated by the ER stress response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 73 publications
3
33
0
Order By: Relevance
“…Similarly, studies have implicated Ire1␣ in modulation of ER stress-induced cell death. It has been shown that, in ER-stressed cells, XBP1 splicing and XBP1 protein expression decline with time (24,25,35). This decline correlates with cell death, and reconstitution of Ire1␣ activity improves cell survival (15,18).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, studies have implicated Ire1␣ in modulation of ER stress-induced cell death. It has been shown that, in ER-stressed cells, XBP1 splicing and XBP1 protein expression decline with time (24,25,35). This decline correlates with cell death, and reconstitution of Ire1␣ activity improves cell survival (15,18).…”
Section: Discussionmentioning
confidence: 99%
“…According to the general concept [36,[41][42][43], appearance of abnormal protein leads to the dissociation of GRP78/BiP-IRE1, thereby IRE1 forms a dimer in the ER membrane, exhibits the RNase activity and splices the uncut XBP-1, which produces active XBP-1s. Its translation product XBP-1s has been reported to lure molecular chaperones under the control of the ER stress response element (ERSE) [44]. We suppose that such processes took place in the present cells.…”
Section: Grp78/bipmentioning
confidence: 97%
“…Real-time quantitative reverse transcription (qRT)-PCR was used to measure gene transcript levels as previously described, 53 using commercially available pre-validated primers (Origene, Rockville, MD, USA) for NLRP1, IPAF-1, and AIM2. THP-1 monocyte mRNA was used as internal control for experiments.…”
Section: Methodsmentioning
confidence: 99%